Bees in early modern transatlantic literature : sovereign colony - Jacobs, Nicole A. (New York, NY : Routledge, 2021)
This book examines apian imagery--bees, drones, honey, and the hive--in the seventeenth- and eighteenth-century literary and oral traditions. In England and the New World colonies during a critical period of expansion, the metaphor of this communal society faced unprecedented challenges even as it came to emblematize the process of colonization itself. The beehive connected the labor of those marginalized by race, class, gender, or species to larger considerations of sovereignty. This study examines the works of William Shakespeare; Francis Daniel Pastorius; Hopi, Wyandotte, and Pocasset cultures; John Milton; Hester Pulter; and Bernard Mandeville. Its contribution lies in its exploration of the simultaneously recuperative and destructive narratives that place the bee at the nexus of the human, the animal, and the environment. The book argues that bees play a central representational and physical role in shaping conflicts over hierarchies of the early transatlantic world.
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgments -- Introduction: Abusing the Hive -- 1 Bee Time: Shakespeare -- 2 Hive Split: The New World Colonists -- 3 Stingless and Stinging: Native American Kinship -- 4 Honey Production and Consumption: Milton -- 5 Worker Bee Sacrifice: Pulter -- Conclusion: The Transatlantic Grumbling Hive -- Bibliography -- Index
OCLC-licensed vendor bibliographic record.
Keywords: English literature -- 17th century -- History and criticism; English literature -- 18th century -- History and criticism; American literature -- 17th century -- History and criticism; American literature -- 18th century -- History and criticism; Bees in literature; Literature and society -- England; Literature and society -- United States; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh